2008
DOI: 10.1248/jhs.54.43
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Ascorbic Acid in Neural Differentiation and Development: High Levels of Ascorbic Acid 2-Glucoside Effectively Enhance Nerve Growth Factor-Induced Neurite Formation and Elongation in PC12 Cells

Abstract: The aim of this study was to investigate the role of ascorbic acid (AsA) in neural differentiation induced by nerve growth factor (NGF) in PC12 cells, a neural precursor cell line. Cells were cultivated in the presence of L-ascorbic acid-2-O-α-D-glucopyranoside (AA-2G) and evaluated for potentiation of neural differentiation induced by a small amount of NGF. AA-2G enhanced the proportion of neurite-bearing cells in a concentration-dependent manner (<1 mM). When cultivated with relatively high concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The authors found that relatively high concentrations of ascorbic acid in the brain not only promote NGF-induced differentiation of neural precursor cells but also participate in the development of neural network-forming cells (38). Further studies will explain the key mechanism for the improved behavioural effects seen in rats after the administration of ascorbic acid.…”
Section: Discussionmentioning
confidence: 95%
“…The authors found that relatively high concentrations of ascorbic acid in the brain not only promote NGF-induced differentiation of neural precursor cells but also participate in the development of neural network-forming cells (38). Further studies will explain the key mechanism for the improved behavioural effects seen in rats after the administration of ascorbic acid.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, mouse models have played an important role in the mechanisms involving neurological diseases, especially in clinical studies related to development (Haramoto et al 2008). However, for diseases such as Alzheimer's, these same rodent models have been discarded, especially in some studies on the role of cholesterol in this disease (Ledesma & Dotti 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring plant phenols and flavonoids possess a broad range of pharmacological activities such as antioxidant, antimutagenic, antimicrobial, antiulcer, antiarthritic, anti cancer and protein kinase inhibition (Marinova et al, 2005;Sulaiman and Balachandran, 2012). Free radicals have been found to play a major role in several human diseases, including, brain disorders (Haramoto et al, 2008), as brain is more vulnerable to oxidative stress due to imbalance between reactive oxygen radicals and antioxidant defence system of our body (Hotta et al, 2002). Exhaustive pharmacological work has been conducted where polyphenols have been reported to possess (Fernandez et al, 2006;Viola et al, 1995;Saaby et al, 2009).…”
Section: Resultsmentioning
confidence: 99%